Henry the Young King, 1155-1183 - Strickland, Matthew, 1962- (Yale University Press, 2016)
This first modern study of Henry the Young King, eldest son of Henry II but the least known Plantagenet monarch, explores the brief but eventful life of the only English ruler after the Norman Conquest to be created co-ruler in his father's lifetime. Crowned at fifteen to secure an undisputed succession, Henry played a central role in the politics of Henry II's great empire and was hailed as the embodiment of chivalry. Consistently denied direct rule, the Young King was provoked first into heading a major rebellion against his father, then to waging a bitter war against his brother Richard for control of Aquitaine, dying before reaching the age of thirty having never assumed actual power. This history provides a richly coloured portrait of an all-but-forgotten royal figure tutored by Thomas Becket, trained in arms by the great knight William Marshal, and incited to rebellion by his mother Eleanor of Aquitaine, while using his career to explore the nature of kingship, succession, dynastic politics, and rebellion in twelfth-century England and France.